Electrodeposition of metastable Ag-Rh alloys and study of their hydrogen storage ability in comparison with Pd. (1st May 2018) - Mattarozzi, Luca; Cattarin, Sandro; Comisso, Nicola; Gerbasi, Rosalba; Guerriero, Paolo; Musiani, Marco; Vázquez-Gómez, Lourdes
Abstract: Porous Ag-Rh alloys of intermediate compositions in the metallurgic miscibility gap have been electrodeposited from mildly acid sulphate baths of the two metal ions (pH ≅ 3.3). The morphology revealed by SEM is microporous; XRD data are consistent with the formation of prevalent phases with lattice parameters depending on composition according to Vegard's law. Alloys with a predominant phase of composition Ag47 Rh53 – estimated from XRD peaks position – are deposited from a bath containing 0.25 M Na2 SO4 + 1 mM Ag2 SO4 + 3 mM Rh2 (SO4 )3 . Voltammograms recorded with Ag-Rh alloys in 0.1 M H2 SO4 show analogies with those obtained with Pd and Rh, but no clear evidence of the absorption and storage of hydrogen atoms in the alloy material, in contrast with recent literature claims of hydrogen charging of Ag-Rh nanoparticles. Graphical abstract: Highlights: Easy room temperature preparation of metastable Ag-Rh alloys. Deposition of a predominant single phase alloy without additives. Voltammetric investigation of hydrogen loading in Pd and in Ag-Rh alloys. Estimate of H adsorption phenomena at Ag-Rh nanoparticles.